Efektivitas Media Bergerak Aplikasi Plotagon dalam Pembelajaran Insya’ Muwajjah - Muhammad Hafidz; Firyal Anggraini Syarif (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2026)
This study investigates the impact of the animated media Plotagon on improving students' writing skills. The research involved eighth-grade class A (21 male students) and class B (16 female students) as the study sample. A pre-test was conducted before the implementation of learning using Plotagon, followed by the application of the learning procedures and a post-test. The learning process included opening, core, and closing activities, where students interacted with the lesson material through observing explanations, watching animated videos, and asking questions. The results of the post-test showed a significant improvement in writing skills, with students scoring higher compared to the pre-test. Furthermore, the validity and reliability of the research instruments were analyzed using Excel, confirming the reliability of the results. Based on hypothesis testing, the study found that the use of Plotagon had a positive impact on improving students' writing skills, with an average N-gain score of 75.89, indicating high effectiveness. Plotagon Animation Media